BAGAIMANA KEUANGAN ISLAM MENGGUNAKAN FAKTOR DISKONTO DALAM CAPITAL BUDGETING DECISION? - Hanesti, Elsi Mersilia (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2018)
In the conventional financial management, the method of calculating the capital budgeting decision using NPV and IRR, which both use the interest rate as one of its component count (as a discount factor). Then, how Islamic financial management sees this? With the research methods of literature study, this paper is about the financial outlook of Islam the methods of NPV and IRR as well as finding out what the proper method for capital budgeting decision. Results of the study were that in the process capital budgeting decision, the use of NPV and IRR methods are allowed (according Obaidullah, Prof. Shabir F.Ulgener, and Zarqa). The interest rate in the calculation only as a means of simplification and ease in the calculation. The use of a list of compound interest rate (compounded interest) is a tool to calculate the expected rate today and the future. It can be said that the Islamic finance uses a list of compound interest rate as a tool for simplify the calculation, just as a comparison level of opportunity cost in alternative investments. The level of interest in the calculation of these can be replaced with a comparator, such as: the return on the sukuk, the profit sharing ratio, and the return on investment or other real instruments in Islam.